Proceedings of the International Conference on Microplastic Pollution in the Mediterranean Sea (Springer Water,, 2018)
This book focuses on different aspects of microplastic pollution, offering authors and readers the opportunity to share their knowledge, identify issues and propose solutions and actions to face this environmental threat. Although plastic pollution is a well-known global problem, the recent discovery of microplastics and nanoplastics in seas and oceans represents a very alarming new environmental challenge. The book offers comprehensive insights into the origins of the problem, its impact on marine environments, particularly the Mediterranean Sea and coasts, and the current research trends aimed at finding technical solutions to mitigate the phenomenon. It is primarily intended for scientists and decision makers from industry, international, national and local institutions and NGOs.